FERTILITY RATE USING THE PALMORE FORMULA IN EAST JAVA PROVINCE: A STUDY OF 2015 SUPAS - Muhammad Abdul Khafidz Maftukh; Lutfi Agus Salim; Farizah Mohd Hairi (Universitas Airlangga, 2021)
Fertility is an important indicator for the success of state development, especially in the health sector. It can be estimated through direct and indirect methods. This study aimed to determine the fertility rate in East Java province indirectly using the Palmore Formula. This study was a descriptive analysis using secondary data from the 2015 Inter-census Population Survey / Survei Penduduk Antar Sensus (SUPAS). It calculated the rate directly and manually. The Total Fertility Rate (TFR) was at 2.02 per two children born by each mother in East Java province. It was compared with the national average published by the Central Bureau of Statistics within 5 periods of SP1990, SUPAS 1995, SP2000, SUPAS 2005, and SP2010. In each period, the rate was lower without any difference. The Palmore Formula is considered a good method for estimating fertility rates.